Altered Coupling Between Resting-State Cerebral Blood Flow and Functional Connectivity Strength in Cervical Spondylotic Myelopathy Patients - Wei, Wuzeng; Wang, Tao; Abulizi, Tuersong; Li, Bing; Liu, Jun (Frontiers in Neurology, 2021)
Background: Changes in regional neural activity and functional connectivity in cervical spondylotic myelopathy (CSM) patients have been reported. However, resting-state cerebral blood flow (CBF) changes and coupling between CBF and functional connectivity in CSM patients are largely unknown. Methods: Twenty-seven CSM patients and 24 sex/age-matched healthy participants underwent resting-state functional MRI and arterial spin labeling imaging to compare functional connectivity strength (FCS) and CBF between the two groups. The CBF–FCS coupling of the whole gray matter and specific regions of interest was also compared between the groups. Results: Compared with healthy individuals, CBF–FCS coupling was significantly lower in CSM patients. The decrease in CBF–FCS coupling in CSM patients was observed in the superior frontal gyrus, bilateral thalamus, and right calcarine cortex, whereas the increase in CBF–FCS coupling was observed in the middle frontal gyrus. Moreover, low CBF and high FCS were observed in sensorimotor cortices and visual cortices, respectively. Conclusion: In general, neurovascular decoupling at cortical level may be a potential neuropathological mechanism of CSM.